Modeling turbocharger of marine diesel generator engine in steady load conditions - Nguyen, Quang Vinh (2020)
This paper presents a model of the turbocharger for a marine diesel generator engine which used on ships. Based on the laws of thermodynamics, mean value model and Matlab/Simulink computational environment, the submodelshave been built torepresent for components of theturbocharger, and acomplete model includingthe submodels and their relationshipsdescribes the turbocharger's internal performances. The diesel - turbocharger combination is simulated at some usual operation modes at different steady loads (0% - 100%) with constant speed. At each regime of load, the key characteristics are varied, for example mass flow, turbine speed, efficiency and temperature. In the practical operation, these parameters are important to evaluate engine conditions, however they are very difficult to measure. Therefore,this is meaningful in predicting turbocharger operations and maintenance activities.